HIV/AIDS-related stigma, discrimination and human rights violations amongst patients attending ARV clinic in Tshwane District Hospital - Ogunjiofor, Asinobi Chukwuemeka Cyril (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MPhil )--University of Stellenbosch, 2011.